Pareisactus evrostos, a new basal iguanodontian (Dinosauria: Ornithopoda) from the Upper Cretaceous of southwestern Europe - Párraga, Javier; Prieto-Márquez, Albert (Zootaxa, 2019)
We describe a new genus and species of a basal iguanodontian ornithopod dinosaur, Pareisactus evrostos, from lower Maastrichtian strata of the Conques Formation in the south-central Pyrenees of northeastern Spain. This animal is solely represented by a scapula characterized by having a dorsoventral extent of the proximal constriction as deep as it is thick; a lateral surface of the proximal region of the scapula under the acromion process forming a deep and thick roof over an extremely deep deltoid fossa; and a long apex of the glenoid that accounts for half of the maximum depth of the proximal region of scapula. Pareisactus is recovered as a member of Rhabdodontidae, sharing with Rhabdodon a well-demarcated deltoid ridge. P. evrostos represents the seventh species of rhabdodontid in Europe and third specimen of this endemic clade of European iguanodontians in the eastern Tremp Syncline of the southern Pyrenean region. [Zoobank registration: genus Pareisactus: urn:lsid:zoobank.org:act:0ACDCF80-1ECF-4EEF-8A77-9297CB7A1572, species P. evrostos: urn:lsid:zoo bank.org:act:8CB207EE-30CF-421D-A611-75DB57E92054]